Quality of Croatian Inland Bathing Areas: Reference to The Region and EU - Dominik Galić; Arijana Cenov; Dražen Lušić; Marin Glad; Slaven Jozić; Bruno Cvetković; Daniel Maestro; Nerma Maestro; Diana Mance; Darija Vukić Lušić (Journal of Health Sciences, 2021)
Introduction: The Republic of Croatia (HR) has significantly invested in monitoring the quality of inland bathing areas during the past 10 years. The aim of this paper was to analyze the results obtained during the 2014-2019 period and to compare them with the Region (non-European Union [EU] countries neighboring Croatia) and EU. Moreover, bathing water quality data at two bathing areas of Zagreb (lakes Jarun and Bundek) were processed in more detail. Methods: The quality of inland bathing areas in the HR is monitored in five rivers and five lakes in nine Croatian counties; 19 of the 35 monitored sites are located in Zagreb County. Escherichia coli (EC) was determined by EN ISO 9308-3: 1998, while intestinal enterococci (ENT) were defined by EN ISO 7899-2: 2000. Statistical processing of the results was performed using the Microsoft Excel Statistical Package (Redmond, USA) and Statistica 13.5. (Stat.Sof.Inc., Tulsa, USA); the significance level was set to p < 0.05. Results: During the study period, the worst Croatian inland water quality was recorded in 2019 (excellent quality for only 25.9% of the bathing areas), while the best quality was recorded in 2015 (excellent quality in 57.1%). On average (2014-2019), the share of bathing areas with excellent quality in Croatia was 46.3% (i.e., under the EU average of 85.3%); with no poor locations (EU average was nearly 2%). A significant positive correlation was found between fecal indicators (EC&ENT) and the amount of precipitation, while a negative correlation with water and air temperature in lakes. Conclusions: The quality of Croatian inland bathing areas is significantly lower than the European average, while EU water quality is improving. Regarding the countries bordering Croatia, Italy, Slovenia, and Hungary have achieved better results, while Montenegro, Serbia, and Bosnia and Herzegovina are still in the process of developing the monitoring of the bathing water quality.